2014
DOI: 10.2519/jospt.2014.0303
|View full text |Cite
|
Sign up to set email alerts
|

Heel Pain—Plantar Fasciitis: Revision 2014

Abstract: The Orthopaedic Section of the American Physical Therapy Association (APTA) has an ongoing effort to create evidence-based practice guidelines for orthopaedic physical therapy management of patients with musculoskeletal impairments described in the World Health Organization's International Classification of Functioning, Disability, and Health (ICF). The purpose of these revised clinical practice guidelines is to review recent peer-reviewed literature and make recommendations related to nonarthritic heel pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
368
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 274 publications
(377 citation statements)
references
References 88 publications
3
368
1
5
Order By: Relevance
“…The patient reported plantar pain during the initial steps after a period of inactivity, which is often reported in patients diagnosed with PF, 1 and reduction of this pain is an important outcome in a patient-centered approach. A visual analog scale is used to measure pain, and it has been suggested that a change of 19 mm is the minimum measurement to indicate a clinical improvement in pain during these first steps.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The patient reported plantar pain during the initial steps after a period of inactivity, which is often reported in patients diagnosed with PF, 1 and reduction of this pain is an important outcome in a patient-centered approach. A visual analog scale is used to measure pain, and it has been suggested that a change of 19 mm is the minimum measurement to indicate a clinical improvement in pain during these first steps.…”
Section: Discussionmentioning
confidence: 92%
“…The PF diagnosis was made from the patient history and a physical examination, which was consistent with published PF guidelines. 1 The woman had a body mass index of 31.2 kg/m 2 and was physically active (jogging), with no hormonal dysfunction or rheumatic disease. The patient reported plantar medial heel pain and tenderness at the calcaneal tuberosity.…”
Section: Case Reportmentioning
confidence: 99%
See 3 more Smart Citations